The Problem of Evil in DC Universe Animated Movies, 2007-2016. DC Multiverse, an Ironic Illustration of Leibniz's Theodicy? The Problem of Evil in DC Universe Animated Movies, 2007-2016 - Toufic Ishaya El-Khoury (Journal for Religion, Film and Media, 2017)
This article explores the question of evil and its metaphysical and moral implications in a series of animated movie adaptations of the DC Universe produced since 2006. The contemporary evolution of the medium, called the "Iron Age of comics", has seen the auto-reflexive nature of comics produce problems and themes related to the main question discussed in Christian theodicy: how can we perceive and define the possibility of evil in a world where God's omnipotence should have eliminated such a possibility? Moreover, why does evil seem to spread indefinitely in spite of all the efforts deployed by superheroes to stop evil? We will discuss the problem of evil as a natural narrative topic in light of comics' mythological and religious roots and with a particular study case: DC Comics Multiverse as an illustration of Leibniz's "best of all possible worlds" argument.